2013
DOI: 10.7314/apjcp.2013.14.8.4847
|View full text |Cite
|
Sign up to set email alerts
|

Is FDG -PET-CT A Valuable Tool in Prediction of Persistent Disease in Head and Neck Cancer

Abstract: Objectives: To evaluate accuracy of FDG-PET CT in prediction of persistent disease in head and neck cancer cases and to determine prognostic value of metabolic tumor response. Materials and Methods: Between 2009 and 2011, 46 patients with squamous cell carcinoma of head and neck receiving PET-CT were treated with definitive radiotherapy, with or without chemotherapy. There were 29 nasopharyngeal, 11 hypopharyngeal, 3 oropharyngeal and 3 laryngeal cancer patients, with a median age of 50.5 years (range 16-84), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…There is controversy regarding the value of PET/CT in evaluating therapeutic effects on cancers. Some have stated that FDG PET/CT was a valuable tool for assessing treatment responses [21, 51]. 18 F-FDG uptake was increased in hyperglycolyzed regions, but the exact mechanisms were complex and influenced by several microenvironmental parameters, such as the intracellular 18 F-FDG phosphorylation capability, tumor oxygenation status, GLUT activity, blood flow and permeability [5254].…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy regarding the value of PET/CT in evaluating therapeutic effects on cancers. Some have stated that FDG PET/CT was a valuable tool for assessing treatment responses [21, 51]. 18 F-FDG uptake was increased in hyperglycolyzed regions, but the exact mechanisms were complex and influenced by several microenvironmental parameters, such as the intracellular 18 F-FDG phosphorylation capability, tumor oxygenation status, GLUT activity, blood flow and permeability [5254].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and animal studies have shown that hyperglycemia promotes tumor growth and proliferation (Nunez et al, 2006;Liu et al, 2011). Indeed, this is the basis for Positron Emission Tomography/Computed Tomography (PET/CT), which enables detection of potentially cancerous cells based on their greater uptake of glucose (Gambhir, 2002;Uzel et al, 2013). A prospective cohort study in Sweden also reported that abnormally elevated fasting glucose and postload glucose levels are associated with an increased risk of cancer incidence in females (Stattin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also it has become an important tool for the detection of bone metastasis (Liu et al, 2013 18-F-FDG accumulation rate evaluated by PET and patient prognosis. The standardized uptake value (SUV) is a semiquantitative simplified measurement of the tissue FDG accumulation rate, and the recent studies of the head-and-neck, esophagus, lung, and cervical cancer have explored the prognostic significance of the maximum standardized uptake value (SUVmax) (Sasaki et al, 2005;Lee et al, 2009;Ma et al, 2013;Uzel et al, 2013;Zhu et al, 2013). Although several number of studies have investigated the usage of PET/CT in the evaluation of RC, its connection with tumor size and nuclear grade are not researched enough in literature.…”
Section: Introductionmentioning
confidence: 99%